2010
DOI: 10.1104/pp.110.154773
|View full text |Cite
|
Sign up to set email alerts
|

Root-Specific Expression ofOsNAC10Improves Drought Tolerance and Grain Yield in Rice under Field Drought Conditions    

Abstract: Drought poses a serious threat to the sustainability of rice (Oryza sativa) yields in rain-fed agriculture. Here, we report the results of a functional genomics approach that identified a rice NAC (an acronym for NAM [No Apical Meristem], ATAF1-2, and CUC2 [Cup-Shaped Cotyledon]) domain gene, OsNAC10, which improved performance of transgenic rice plants under field drought conditions. Of the 140 OsNAC genes predicted in rice, 18 were identified to be induced by stress conditions. Phylogenic analysis of the 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
490
0
18

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 714 publications
(555 citation statements)
references
References 46 publications
22
490
0
18
Order By: Relevance
“…We have previously identified stress-regulated genes in rice plants through expression profiling using the Rice 39-Tiling microarray (GreenGene Biotech) and RNAs from the 14-d-old leaves of rice seedlings subjected to drought, high salt, and low temperature (Oh et al, 2009;Jeong et al, 2010). In addition to up-regulated genes, we also identified many genes that were down-regulated under stress conditions, including most of the photosynthetic genes involved in light and dark reactions.…”
Section: Smd Of Photosynthetic Genes During Stress Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously identified stress-regulated genes in rice plants through expression profiling using the Rice 39-Tiling microarray (GreenGene Biotech) and RNAs from the 14-d-old leaves of rice seedlings subjected to drought, high salt, and low temperature (Oh et al, 2009;Jeong et al, 2010). In addition to up-regulated genes, we also identified many genes that were down-regulated under stress conditions, including most of the photosynthetic genes involved in light and dark reactions.…”
Section: Smd Of Photosynthetic Genes During Stress Conditionsmentioning
confidence: 99%
“…Each plant was grown in a pot (4 3 4 3 5 cm 3 ; six plants per pot) filled with rice nursery soil (Bio-Media) for 14 d after germination. Stress treatments were performed as described previously (Oh et al, 2009;Jeong et al, 2010;Redillas et al, 2011). Briefly, for drought stress, 14-d seedlings were air dried in the greenhouse under continuous light of approximately 900 to 1,000 mmol m 22 s 21 .…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%
“…QTL QSnp3a controlling SpNP detected in the two sets of ILs, and QSf3, QFgwp3 and QGyp3 for SF, FGWP and GYP detected in the TQ-ILs were mapped together with OsTIFY11a in the region of 3502670-4681740 on chromosome 3, which encodes a ZIM family gene exhibiting significant improvement in tolerance against drought and high salinity when overexpressed in transgenic rice plants (Ye et al 2009). QTL QSnp11 affecting SpNP detected in the two sets of ILs, and QFgwp11a and QGyp11 underlying FGWP and GYP detected in the TQ-ILs, were mapped together with two NAC TF genes in the region of 749467-1767997 on chromosome 11, OsNAC10, which was associated with significantly increased DT (Jeong et al 2010), and OsNAC045, which could be induced by drought, high salinity and abscisic acid (Xiao et al 2007;Zheng et al 2009). QTL QPh9 governing PH, which was localised in 17141056-18060875 on chromosome 9 in TQ-ILs, was mapped together with OsbZIP72 encoding a zinc-finger TF, which was a positive regulator of ABA response and DT in rice ).…”
Section: Comparison Of Identified Dt Qtls With Dt-related Genes In Eamentioning
confidence: 99%
“…NAC TFs have been reported during drought in rice (Rabbani et al, 2003;Zhou et al, 2007) and Arabidopsis (Matsui et al, 2008;Tran et al, 2010). The use of NAC TFs as tools to improve drought tolerance in rice (Hu et al, 2006;Jeong et al, 2010;Zheng et al, 2009), tobacco (Ramegowda et al, 2012), wheat (Xue et al, 2011), and Arabidopsis (Gao et al, 2010) has also been reported.…”
Section: Nac Tf Familymentioning
confidence: 99%
“…Overexpression of another rice SNAC gene, SNAC2, showed tolerance to polyethylene glycol (PEG), cold, and salinity treatments in the rice seedlings (Hu et al, 2008). In a separate field trial, there was a 42% increase in grain yield in OsNAC10-overexpressing transgenic rice under drought conditions ( Jeong et al, 2010). Heterologous expression of rice SNAC1 in transgenic wheat resulted in improved drought tolerance of transgenic rice under controlled growth conditions (Saad, 2013).…”
Section: Nac Tf Familymentioning
confidence: 99%